Fluid Bodies and Bodily Fluids in Premodern Europe Bodies, Blood, and Tears in Literature, Theology, and Art - Barbezat, Michael David; Scott, Anne M. 1940-2021 (Arc Humanities Press, 2019)
This interdisciplinary collection of essays, containing chapters from specialists in history, art history, medical history, and literature, examines how the intimately familiar language of the body served as a convenient medium through which to imagine and describe transformations of the larger world, both for the better and also for the worse. Its individual contributors demonstrate the myriad ways in which rethinking the human body was one way to approach rethinking the social, political, and religious realities of the world from the Middle Ages until the early modern period
Description based on online resource; title from PDF title page (publisher's Web site, viewed 21. Dez 2019)
Keywords: Blood; bodily humours; corporeality; devotion; emotions; tears; HISTORY / Renaissance; Theologie; Blut -- Motiv; Weinen -- Motiv; Körper -- Motiv; Kunst; Literatur; Europa; Aufsatzsammlung